Eksistensi Pemerintahan Nagari di Sumatera Barat Dalam Kajian Sejarah - Harisnawati harisnawati; Sri Rahayu; Intan Sri Wahyuni (Bakaba, 2018)
Motivated by the birth of various problems that arise related to various regulations that were created by the nagari. As a "mini republic", the nagari no longer have the same autonomy as in ancient times. The strengthening of the central government system has influenced the governance of the village, so that the village is more merely an extension of the central government system. This can be seen from the birth of Law No. 5 of 1979 concerning Village Government, which no longer makes the village the lowest level of government in West Sumatra. The return of the lowest system of government in West Sumatra to the governance of the Nagari through Law No. 22 of 1999 concerning Regional Autonomy which was then followed by Regional Regulation No. 9 of 2000 concerning Basic Provisions of the Nagari Government, which subsequently was renewed by Law No. 32 of 2004 concerning Regional Government, which was then also followed by a revision of the Regional Regulation No. 2 of 2007 concerning the Principles of the Nagari Government. But returning to the nagari government only changes the nomenclature, and the nagari government system continues to run as it was with the previous village government system. Birth of Law No. 6 of 2014 concerning Villages followed by Regional Regulation of the Province of West Sumatra No. 7 of 2018 concerning Nagari strengthened the existence of the Nagari government system as a Desa Adat. This Regional Regulation adopts a number of values which have become important characteristics of an adat government.